STUDY ON THE CONSERVATION OF HISTORICAL PATRIMONY AT VERA CRUZ CEMETERY, PASSO FUNDO/RS - Lorenzet Galvan, Ana Carolina (2020)
This paper aims to discuss heritage preservation and interventions in the cemetery space, taking the Vera Cruz Cemetery, of Passo Fundo/RS, as a field of study, understanding the cemetery as an open-air museum. We opted for a dialogue between History, Art and Heritage, cataloging tombs and funerary typologies. We catalog the most expressive ones according to criteria determined during the research, to contextualize the symbolic and allegorical representations present in the cemetery. We also discussed the possibilities of intervention in the cemetery space, problematizing the actions of third parties in the tombs and their implication in the funerary heritage and its symbolic and representative set. Thus, it is clear that the intervention, if carried out in line with historical research, helps to preserve and enhance patrimony.